2015
DOI: 10.3109/19401736.2015.1110805
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Aconitum chiisanense Nakai (Ranunculaceae)

Abstract: The herbal medicinal genus Aconitum L., belonging to the Ranunculaceae family, represents the earliest diverging lineage within the eudicots. It currently comprises of two subgenera, A. subgenus Lycoctonum and A. subg. Aconitum. The complete chloroplast (cp) genome sequences were characterized in three species: A. angustius, A. finetianum, and A. sinomontanum in subg. Lycoctonum and compared to other Aconitum species to clarify their phylogenetic relationship and provide molecular information for utilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…The complete chloroplast genome of A. carmichaelii was 154,776 bp in size (GenBank accession number KY006977) with 38.1% overall GC content. The genome structure was highly similar to the reported chloroplast genome of closely related species A. chiisanense (Lim et al 2015), and contained 83 proteincoding genes, 35 tRNA genes, and 8 rRNA genes. The chloroplast genome was composed of a large single-copy (LSC), a small single-copy (SSC), and two inverted repeat (IR) regions of 86,330bp, 15,986 bp and 26,193 bp, respectively.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The complete chloroplast genome of A. carmichaelii was 154,776 bp in size (GenBank accession number KY006977) with 38.1% overall GC content. The genome structure was highly similar to the reported chloroplast genome of closely related species A. chiisanense (Lim et al 2015), and contained 83 proteincoding genes, 35 tRNA genes, and 8 rRNA genes. The chloroplast genome was composed of a large single-copy (LSC), a small single-copy (SSC), and two inverted repeat (IR) regions of 86,330bp, 15,986 bp and 26,193 bp, respectively.…”
supporting
confidence: 59%
“…Thirtythree genes (14 tRNA, 8 rRNA, and 11 protein-coding genes) were duplicated in two inverted repeat regions. As in the chloroplast genomes of other Ranunculaceae species reported (Lim et al 2015;Park et al 2015), the rpl32 gene was lost in A. carmichaelii.…”
mentioning
confidence: 82%
“…A total of 22 genes (8 tRNA and 14 protein-coding genes) contained one or two introns. The maximum likelihood tree constructed using 79 non-redundant protein-coding genes in cpDNAs from 12 Ranunculaceae species and two outgroup species indicated that the cp genome of A. austrokoreense is closely related to the cp DNA of A. chiisanense that we reported recently (Lim et al 2015; Figure 1). Furthermore, sequence comparison identified several distinct sequence variations in proteincoding genes of Aconitum species.…”
mentioning
confidence: 59%
“…Lycoctonum as well as 10 species from the subg. Aconitum (Choi et al, 2016;Kim et al, unpublished;Lim et al, 2017;Yang, unpublished;Yang et al, unpublished) (Table 1). Altogether, 14 species and 2 varieties in both subgenera of Aconitum were used for annotation (Table 1).…”
Section: Chloroplast Genome Sequencing Assembly and Annotationmentioning
confidence: 98%
“…hispidum, and A. barbatum var. puberulum were collected from China (Chen et al, 2015), A. reclinatum came from the United States (Kong et al, 2017a), while the remaining species were all sampled from Korea (Choi et al, 2016;Kim et al, unpublished;Lim et al, 2017;Yang, unpublished;Yang et al, unpublished). Chloroplast genome sequences of Aconitum species from Europe were not available in GenBank.…”
Section: Chloroplast Genome Sequencing Assembly and Annotationmentioning
confidence: 99%